Natural variation at OsCERK1 regulates arbuscular mycorrhizal symbiosis in rice. Issue 4 (3rd October 2019) - Huang, Renliang; Li, Zheng; Mao, Cui; Zhang, Hui; Sun, Zhongfeng; Li, Hao; Huang, Congcong; Feng, Yong; Shen, Xianhua; Bucher, Marcel; Zhang, Zhongming; Lin, Yongjun; et al.
Summary: The symbiotic interaction between arbuscular mycorrhizal fungi (AMF) and land plants is essential for efficient nutrient acquisition and utilisation. Our understanding of key processes controlling the AMF colonisation in rice is still limited. Dongxiang wild rice (DY) exhibited a stronger colonisation with Rhizophagus irregularis than the rice cultivar Zhongzao 35 (ZZ35). Chromosome segment substitution lines were constructed and the OsCERK1 gene from DY was mapped. Transgenic plants in the japonica rice Zhonghua 11 (ZZ11) were constructed to compare root colonisation by AMF. Chromosome single‐segment substitution lines containing OsCERK1 DY showed higher phosphorus content and grain yield relative to ZZ35. Four amino acids substitutions were identified among the OsCERK1 haplotypes of DY, ZZ35 and ZH11 and two of these were in the second lysine‐motif domain, which is essential for the differences of AMF colonisation level among rice varieties. Heterologous expression of OsCERK1 DY in ZH11 significantly enhanced AMF colonisation and increased resistance against the pathogenic fungi Magnaporthe oryzae . Notably, the OsCERK1 DY haplotype was absent from 4660 cultivated rice varieties. We conclude that OsCERK1 is a key gene affecting the symbiotic interaction with AMF and OsCERK1 DY has the biotechnological potential to increase rice phosphorus acquisition and utilisation efficiency for sustainable agriculture. Abstract : See also the Commentary on this article by Lefebvre, 225 : 1404–1406 .